Differences in single badminton player profile between London 2012 and Rio 2016 Olympics Games - Blanca-Torres, J.-C.; Kondric, M.; Fernández-Garcia, A. I.; Cabello-Manrique, D. (Science and Racket Sports VI, 2019)
The purpose of the study was to compare the profile of top world level badminton single matches between the London 2012 and Rio de Janeiro 2016 Olympic Games to observe the evolution of player profile. Players were the best on the world at the time they were selected (81 males and 86 females). Age (months), height (m), mass (kg) and BMI (kg/m2) were determined. No differences were founded in any variable. However, the mean age in male players was lower in London (324,8±37,8 months) than in Rio (337,2±48,8 months). The average mass in male players was lower in London (71,6±7,4 kilos) than in Rio (74,0±7,1 kg). The profile in female badminton player is very similar in both Olympic Games. Knowing the profile of the player throughout the Olympic Games contributes to a better knowledge of this sport discipline.